2021
DOI: 10.21203/rs.3.rs-406829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Erector Spinae Plane Block on Perioperative Opioid Consumption and Rehabilitation in Video Assisted Thoracic Surgery

Abstract: Background The present study aimed to observe whether the ultrasound-guided continuous erector spinae plane block (ESPB) has an effect on opioid consumption and postoperative rehabilitation in patients who undergo video-assisted thoracic surgery (VATS).Methods In this prospective study, 120 patients aged 20–70 yrs, undergoing elective VATS, were randomly allocated to one of three groups: Group C (General anaesthesia with patient-controlled intravenous analgesia [PCIA]), Group T (General anaesthesia with patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…still accepted gold standard method in the treatment of post-thoracotomy pain [4]. However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…still accepted gold standard method in the treatment of post-thoracotomy pain [4]. However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [5].…”
mentioning
confidence: 99%
“…However, serious complications such as dural puncture, sympathetic block, spinal hematoma, and epidural abscess can also be seen due to epidural application [5]. Thoracic paravertebral block (TPVB) application has also been used in recent years due to the lower incidence of side effects such as hypotension, urinary retention, and nausea and vomiting compared to TEA [4,6]. With the widespread use of ultrasound (US) in recent years, different thoracic wall block techniques, which are claimed to cause fewer complications, have begun to be applied [7].…”
mentioning
confidence: 99%
“…Our findings are consistent with the previous study that postoperative pain at rest and coughing in continuous ESP block were significantly higher than TEA 24 hours after surgery. 28 On the contrary, Nagaraja et al 10 have reported comparable pain scores in both TEA and ESP block groups in the early postoperative period after cardiac surgery and that an ESP block might be superior to TEA at 24 h, 36 h, and 48 h, both at rest and while coughing.…”
mentioning
confidence: 95%